2012
DOI: 10.1080/17458080.2011.577099
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular biosynthesis, characterisation and in-vitro antibacterial potential of silver nanoparticles using Agaricus bisporus

Abstract: Microbial silver nanoparticles have been known to have bactericidal effects but the antimicrobial mechanism has not been clearly revealed. The use of microorganisms in the synthesis of nanoparticles emerges as an ecofriendly and exciting approach. Here we report on the extracellular synthesis method for the preparation of silver nanoparticles in water using the extract of Agaricus bisporus, a naturally occurring edible mushroom, as reducing and protecting agents. The silver nanoparticles were characterised by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…In addition, the mushroom produces several enzymes such as lactase and carboxymethylcellulase (CMCase) . Therefore, based on our FTIR spectra, we concluded that the biomolecules (proteins and polysaccharides) present in the filtrate were responsible for the synthesis of PSC‐AgNPs . Pleurotus sajor‐caju extract proved to have an ability to synthesize AgNPs.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, the mushroom produces several enzymes such as lactase and carboxymethylcellulase (CMCase) . Therefore, based on our FTIR spectra, we concluded that the biomolecules (proteins and polysaccharides) present in the filtrate were responsible for the synthesis of PSC‐AgNPs . Pleurotus sajor‐caju extract proved to have an ability to synthesize AgNPs.…”
Section: Discussionmentioning
confidence: 84%
“…57 Therefore, based on our FTIR spectra, we concluded that the biomolecules (proteins and polysaccharides) present in the filtrate were responsible for the synthesis of PSC-AgNPs. 58 Pleurotus sajor-caju extract proved to have an ability to synthesize AgNPs. A comparison between the FTIR spectra of the extract and AgNPs showed slight differences mainly corresponding to carboxy-hydroxyl bond vibrations during the synthesis of PSC-AgNPs.…”
Section: Uv-visible Spectroscopymentioning
confidence: 99%
“…and Klebsiella sp. (Dhanasekaran et al 2013). However, chitosan NPs of A. bisporus had antioxidant effects.…”
Section: Biosynthesis Of Silver Nanoparticles Using Agaricus Bisporusmentioning
confidence: 99%
“…Dhanasekaran et al reported that mycosynthesis of the silver nanoparticle is an earlier and most resourceful elementary method have shown powerful antimicrobial activities; thus nanoparticles can be considered for the use in many medicinal drugs. Mushroom AgNPs have a spherical, core-shell shape; the size ranges from 10 to 70 nm 13 . Sudhakar et al, and Sanghi et al, reported that AgNPs were visually detected due to the color change from yellow to dark brown of the reaction suspension, cell-free filtrate and silver nitrate using SMS showed an organic surface that reduces Ag + and stabilizes the Ag-NPs by using a buried mushroom protein 14,15 .…”
Section: Biosynthesis Of Nobel Metal Nanoparticles By Mushroommentioning
confidence: 99%